Internet Telephony Transport Protocol (ITTP): An Efficient Transport Protocol For Voip Applications - Abu-Alhaj, Mosleh Mohammad (2011)
Over the past few years, the telecommunications sector started moving towards Voice over Internet Protocol (VoIP) technology. VoIP technology employs the internet infrastructure and protocols to transfer VoIP data between call parties. Typically, the RTP applications layer protocol and the UDP transport layer protocol are bound together to address the VoIP applications requirements. However, the RTP/UDP protocols are used to transfer all types of real-time multimedia applications data such as video conferencing, multimedia streaming, voice data, and so on. Therefore, the RTP/UDP protocols are providing information and algorithms that are not needed by the VoIP applications.